ROLE OF ACCREDITATION TO THE PERFORMANCE OF NON COMMUNICABLE DISEASES (NCD’S) CONTROL PROGRAM AND CONTROL IN ACCREDITED AND NON ACCREDITED PRIMARY HEALTH CARE IN CIMAHI DISTRICT - Azni, Nurkarti; Darmawan, Ede Surya (UI Scholars Hub, 2022)
The Non-Communicable Disease (NCD’s) Prevention and Control Program is one of the essential Community Health Efforts implemented by the Puskesmas. Puskesmas accreditation is a form of program to maintain the quality and form of standardization to Puskesmas services in order to provide quality services. This research uses qualitative method, conducted in April-May 2018, aim to see improvement of performance at puskesmas especially at NCD’s Prevention and Control Program. Result of research, in general Output of program of implementation of NCD’s at Puskesmas accredited better than Puskesmas not yet accredited. Community-based partnership and funding activities have not been implemented, Iva test and CBE screening and DM screening are still around 5%, indicating the community and the lack of effective community empowerment. Input components of human resources, facilities, funds, screening instruction implementation are not adequated. Components of Planning Process (P1), Organizing and Moving (P2) at Accredited Puskesmas better than Puskesmas not yet accredited, P3 has been run even though not optimal in some Puskesmas. Need to improve community empowerment to support NCD’s Prevention and Control Program .. It is necessary to encourage the Puskesmas to improve the implementation of Puskesmas Management and conduct Continuous Improvement of Quality to achieve quality improvement as the main basis of Puskesmas Accreditation.